If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 16 = -4 + -4x Solving 16 = -4 + -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. 16 + 4x = -4 + -4x + 4x Combine like terms: -4x + 4x = 0 16 + 4x = -4 + 0 16 + 4x = -4 Add '-16' to each side of the equation. 16 + -16 + 4x = -4 + -16 Combine like terms: 16 + -16 = 0 0 + 4x = -4 + -16 4x = -4 + -16 Combine like terms: -4 + -16 = -20 4x = -20 Divide each side by '4'. x = -5 Simplifying x = -5
| -x+2y-3z=-9 | | -3t+5=26 | | 4x-2x+3-8=7x-5+4x | | 3t+5=26 | | (x^2+y^4)(x^2-y^4)=0 | | 0.67x+7=21 | | 72+36=0 | | 5x-2+8=7x-4 | | 21=8x-75 | | 6a+5x=36 | | (4s+4)(4s-4)=0 | | 3x+y+z=14 | | (3r-1)(4r-3)=0 | | 15-8m=73 | | -8x+6x-7x=3x(4-3)-5x-15 | | 98p=197 | | 5/3= | | 170-2x=25x+20 | | -5=15+4x | | 5x-x+3=-x+7 | | 5-9x=37-16x | | 3n+4=56 | | 3(4i)+2(7i)= | | 3(2x-3)-2x=8-2(3x+1) | | 5x-8-3x-9=-12x+11 | | y^2+4x-4y-12=0 | | 10n+5=9n | | 23+1z=3 | | 3(t+2)=9(t-2) | | e+2(e+4)+3e=56 | | 99-2x=4-9x | | x^2-9xy-10y^2=0 |